THE LOCATING-CHROMATIC NUMBER FOR CERTAIN BARBELL OPERATION ON PIZZA GRAPH AND ITS SUBDIVISION - Irawan, Agus; Asmiati, Asmiati (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
In graph theory, the locating-chromatic number is a parameter that characterizes the minimum number of colors required to assign to the vertices of a graph such that each vertex can be uniquely identified by its color and the colors of its neighbors. The locating-chromatic number of a graph refers to a concept in graph coloring, which involves assigning colors to the vertices of a graph in such a way that adjacent vertices do not share the same color. It represents the minimum number of colors needed for a proper vertex coloring. This study investigates the locating-chromatic number of certain barbell operation on pizza graphs and its subdivisions